On the reliability of mixed LS adjustment models - Even-Tzur, Gilad (Geodesy and Cartography, 2023)
This paper examines the internal and external reliability criteria of the mixed LS adjustment model. We use the reliability concept to quantify the potential for detecting gross errors and to estimate their impact on the adjusted parameters. After a short introduction to the mixed adjustment model, the hat matrix and Baarda’s data snooping we describe the theoretical tools developed to define the internal and external reliability in the mixed adjustment model. The paper presents the results of an example of LS adjustment of transformation parameters between two coordinate systems, indicating that the reliability can be used effectively for this model.